DESIGNING BRAND ACTIVATION THROUGH INSTAGRAM FOR SEMANDTIK - Ridho, Muhammad Ainur (VCD: Journal of Visual Communication Design, 2020)
The purpose of this study is to determine the responses of potential consumers on Instagram to the business value of Semandtik as a social brand. The research method used is the Quantitative Method by conducting questionnaires to 70 respondents and Qualitative Methods to 3 Expert Users, 3 Extreme Users, online observation of 2 competitors, as well as literature and journal studies that can support this research. The results of the study can be concluded that Feeds containing neatly arranged photo/video content and informative and communicative instastories content that can also be accessed are highlighted on profiles are the main factors that make them aware of a brand. Then IGTV and GUIDES features. This is a consideration for semandtik in the future to pay attention to and develop a design and communication strategy in the two Feeds and instastory features, especially in the key-visual and content timeline. On the guides and IGTV features, attention should also be paid to the audience's reference material. Then the majority of respondents are aware of the value brought by semandtik through the statements listed in the semandtik instagram bio and consider the available links to make it easier to access and learn more about semandtik and consider the content presented by semandtik to be quite interesting. Furthermore, Whatsapp is the media most often used to communicate further to a brand on Instagram followed by DM, marketplace, and Website. Keyword: design style, brand Activation, strategic media, batik, artisan.